DESAIN SISTEM INFORMASI PRAKTEK KERJA LAPANGAN MAHASISWA BERBASIS WEB DENGAN METODE SYSTEMS DEVELOPMENT LIFE CYCLE (SDLC) - Hendri Syahputra; Husna Gemasih; Gusfriyanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Field Work Practice is a training facility for informatics engineering students to develop, implement and answer problems faced by their environment. The problem that occurs is where the management and data collection of student data is still carried out semi-systemically because it is recorded in a spreadsheet application so that the data is not structured properly, as a result, information from the placement/assignment process, reporting, and classification of PKL student data is less relevant, accurate and timely. and sometimes human error occurs. Therefore we need a system that is able to make it easier to manage student data from street vendors participants into relevant, accurate and timely information when needed entitled "Web-Based Field Work Practice Information System (PKL). This system is built using the CodeIgniter framework and CSS Layout Bootstrap, then this system will be tested through the blackbox method and compatibility testing. So that we get a system that is able to make it easier to manage student data from street vendors participants into relevant, accurate and timely information when needed.